2020
DOI: 10.3389/fpsyt.2020.00065
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status of Hypothalamic–Pituitary–Thyroid and Hypothalamic–Pituitary–Adrenal Axes in Hospitalized Schizophrenics in Shanghai

Abstract: Objective: Neuroendocrine dysfunction is related to the pathogenesis of mental disorders, but conclusions from clinical research lack consistency. We aimed to investigate the neuroendocrinal pathophysiology and its correlation with clinical symptoms in patients with schizophrenia. Methods:The present cross-sectional study included 486 inpatients with schizophrenia admitted at a psychiatric hospital in Shanghai within one year, and 154 healthy controls (HC) matched on age and gender. The serum hemoconcentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
(63 reference statements)
1
10
0
1
Order By: Relevance
“… 48 Some studies have described thyroid dysfunction in patients with schizophrenia spectrum disorders. 49 , 50 Moreover, there is evidence that patients with first-episode schizophrenia have higher FT3 and FT4 levels than healthy controls, 51 , 52 as well as higher FT3 and FT4 levels and a lower TSH level than patients with recurrence of schizophrenia. 52 However, some investigators have reported that patients with schizophrenia using antipsychotic medications had a lower FT4 level than healthy controls, 26 , 53 and that a lower FT4 level was associated with the use of antipsychotics in regression analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 48 Some studies have described thyroid dysfunction in patients with schizophrenia spectrum disorders. 49 , 50 Moreover, there is evidence that patients with first-episode schizophrenia have higher FT3 and FT4 levels than healthy controls, 51 , 52 as well as higher FT3 and FT4 levels and a lower TSH level than patients with recurrence of schizophrenia. 52 However, some investigators have reported that patients with schizophrenia using antipsychotic medications had a lower FT4 level than healthy controls, 26 , 53 and that a lower FT4 level was associated with the use of antipsychotics in regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…49 , 50 Moreover, there is evidence that patients with first-episode schizophrenia have higher FT3 and FT4 levels than healthy controls, 51 , 52 as well as higher FT3 and FT4 levels and a lower TSH level than patients with recurrence of schizophrenia. 52 However, some investigators have reported that patients with schizophrenia using antipsychotic medications had a lower FT4 level than healthy controls, 26 , 53 and that a lower FT4 level was associated with the use of antipsychotics in regression analyses. 53 Notably, our study detected a significantly higher FT4 level and a significantly lower TSH level only in patients with schizophrenia and agitation and not in those without agitation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to discuss the relationship between the differences of sex in thyroid disease and hyperprolactinemia, we needed to know whether they both signi cantly correlated to sex [16] [31]. We thus recruited patients aged 16 to 40 with sexual characteristics set as a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…The endocrine changes of adrenal and sex steroids may improve cognition in schizophrenia [ 31 , 32 ]. However, testosterone secretion in males goes through a process of natural decline with the recession of testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…For considering the potential interaction effect between the cortisol and testosterone levels, regression analyses showed that the correlation coefficients involving these two predictors were the highest among the regression models. However, the relationship between the C/T ratio and schizophrenia is complicated, relating to the course of disease, age, and duration of antipsychotic medication [ 31 ]. It is also possible that the dosage of antipsychotic drugs, which was not recorded in the present study, has an impact.…”
Section: Discussionmentioning
confidence: 99%